Hypoxia-induced circ_0017521 enhances glycolysis and promotes NSCLC progression via upregulating the PFKFB3/PI3K-AKT pathway - Jian Zhu; Jin Yan; Yuanyuan Zhang; Xiaoli Zhu; Guoping Chen (Mammalian Genome, 2026)

Physics-guided bidirectional synergistic fusion network for stern bearing fault diagnosis in ship propulsion systems - Hongdi Zhou; Yong Pan; Tielin Shi; Jian Duan; Chao Qian; Guoping Yan; Yijie Cai (Ocean Engineering, 2026)

Bacteria–polysaccharide interfacial regulation by calcium alginate hydrogel capsules supports sulfate reduction in acidic water - Yujie Wang; Fangzhou Luo; Zhaoyue Yang; Zhenghua Liu; Huachan Lin; Xiyu Liu; Min Zhang; Guoping Jiang; Lei Zhou; Lechang Xu; Delong Meng; Qingyun Yan; et al. (Carbohydrate Polymers, 2026)

Decolorization of Antarctic krill hydrolysate for salt reduction in surimi gel: improvement of taste, gel properties, and flavor profile - Yurui Zhang; Bo Wang; Yan Li; Xin Jiang; Shangkun Li; Keqiang Lai; Guoping Zhu; Wenzheng Shi (Food Research International, 2026)

Experimental study on the mooring system dynamics of container ships: Coupling effects of wave conditions, Berth locations, and mooring line types - Wanwei Zhang; Guoping Chen; Shichang Yan; Yunpeng Zhu; Jinhai Zheng (Ocean Engineering, 2026)

Otolith chemistry indicates structuring of the Subantarctic myctophid Electrona carlsbergi in the Antarctic Circumpolar Current and Antarctic Slope Current off the South Shetland Islands - Guoping Zhu; Hurui Qian; Lian Wei; Bettina A. Fach; Sophie Bestley; Chenbing Yan; Julian R. Ashford (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Combined influence of strong winds and warm deep water on the formation of Amundsen Sea Polynya in winter - Mengting Zhuo; Yu Hong; Yuhong Zhang; Jiping Liu; Lingqiao Cheng; Guoping Zhu; Song Hu; Yan Du (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Hydrochemical characteristics of carbonated waters and non-carbonated thermal waters of the Heyuan Deep Fault Zone in Guangdong, Southern China - Xianxing Huang; Linjun Xie; Yan Li; Guoping Lu (Geothermics, 2025)

Impact of DNA Extraction Methods on Gut Microbiome Profiles: A Comparative Metagenomic Study - Yanni Pu; Xiaofeng Zhou; Hao Cai; Tao Lou; Chenglin Liu; Mengmeng Kong; Zhonghan Sun; Yanren Wang; Ruyi Zhang; Yuxuan Zhu; Lin Ye; Yuanting Zheng; et al. (Phenomics, 2025)

Fe-mordenite for high-performance N2 rejection - Zhi Yu; Jianing Yang; Seyed Hesam Mousavi; Penny Xiao; Xue Yan; Ali Zavabeti; Yongqiang Wang; Kaifei Chen; Zhe Jefferson Liu; Guoping Hu; Xiaoling Liu; Yu Zhou; et al. (Chemical Engineering Journal, 2024)

Highly luminescent tin-doped manganese halide perovskite nanocrystals for high-resolution patterning and light-emitting diodes - Jiejun Ren; Huiping Liu; Xiaopeng Zhou; Gangyi Zhang; Guoping Yan; Fan Liu; Liangjun Chen; Yuhua Wang (Chemical Engineering Journal, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Sample Collection, DNA Extraction, and Library Construction Protocols of the Human Microbiome Studies in the International Human Phenome Project - Yetong Wang; Ruyi Zhang; Yanni Pu; Danqi Wang; Yanren Wang; Xuemei Wu; Yujie Pan; Chen Luo; Guoping Zhao; Zhexue Quan; Yan Zheng (Phenomics, 2023)

Genomic insights into the genetic basis of cotton breeding in China - Yiqian Li; Zhanfeng Si; Guoping Wang; Zhuolin Shi; Jinwen Chen; Guoan Qi; Shangkun Jin; Zegang Han; Wenhao Gao; Yue Tian; Yun Mao; Lei Fang; et al. (Molecular Plant, 2023)

Exosomes from human urine-derived stem cells carry NRF1 to alleviate bladder fibrosis via regulating miR-301b-3p/TGFβR1 pathway - Junwei Wu; Xinxin Wang; Guoping Fu; Yiyuan Feng; Yan Wang; Guoxian Zhang; Yudong Wu; Lirong Zhang; Hongyu Meng; Jianguo Wen; Bing Zhang; Qingwei Wang (Molecular and Cellular Biochemistry, 2023)

Near-ultraviolet emitters based on carbazole-imidazole for highly efficient solution-processed organic light-emitting diodes - Siyang Liu; Junzi Li; Huibo Yan; Fanghao Ye; Fangfang Niu; Bin Zhang; Guoping Wang; Guijun Li; Pengju Zeng (Chemical Engineering Journal, 2023)

Above- and belowground biomass allocation and its regulation by plant density in six common grassland species in China - Yuanfeng Sun; Yupin Wang; Zhengbing Yan; Luoshu He; Suhui Ma; Yuhao Feng; Haojie Su; Guoping Chen; Yinping Feng; Chengjun Ji; Haihua Shen; Jingyun Fang (Journal of Plant Research, 2022)

A botanical medicine dragon’s blood exhibited clinical antithrombosis efficacy similar to low molecular weight heparin - Jiangbin Liang; Song Mei; Xiangyu Qiao; Wei Pan; Yan Zhao; Shaohui Shi; Yaling Zhai; Haizhao Wen; Guoping Wu; Chengyu Jiang (Science China Life Sciences, 2021)

Transcription Factor VAX1 Regulates the Regional Specification of the Subpallium Through Repressing Gsx2 - Yan Wen; Zihao Su; Ziwu Wang; Lin Yang; Guoping Liu; Zicong Shang; Yangyang Duan; Heng Du; Zhenmeiyu Li; Yan You; Xiaosu Li; Zhengang Yang; et al. (Molecular Neurobiology, 2021)

Homeobox Gene Six3 is Required for the Differentiation of D2-Type Medium Spiny Neurons - Xiaolei Song; Haotian Chen; Zicong Shang; Heng Du; Zhenmeiyu Li; Yan Wen; Guoping Liu; Dashi Qi; Yan You; Zhengang Yang; Zhuangzhi Zhang; Zhejun Xu (Neuroscience Bulletin, 2021)
Medium spiny neurons (MSNs) in the striatum, which can be divided into D1 and D2 MSNs, originate from the lateral ganglionic eminence (LGE). Previously, we reported that Six3 is a downstream target of Sp8/Sp9 in the transcriptional regulatory cascade of D2 MSN development and that conditionally knocking out Six3 leads to a severe loss of D2 MSNs. Here, we showed that Six3 mainly functions in D2 MSN precursor cells and gradually loses its function as D2 MSNs mature. Conditional deletion of Six3 had little effect on cell proliferation but blocked the differentiation of D2 MSN precursor cells. In addition, conditional overexpression of Six3 promoted the differentiation of precursor cells in the LGE. We measured an increase of apoptosis in the postnatal striatum of conditional Six3 -knockout mice. This suggests that, in the absence of Six3, abnormally differentiated D2 MSNs are eliminated by programmed cell death. These results further identify Six3 as an important regulatory element during D2 MSN differentiation.

Multi-proxy evidence of environmental change related to collapse of the Liangzhu Culture in the Yangtze Delta, China - Keyang He; Houyuan Lu; Guoping Sun; Xiang Ji; Yonglei Wang; Kaikai Yan; Xinxin Zuo; Jiangping Zhang; Bin Liu; Ningyuan Wang (Science China Earth Sciences, 2021)

Decoding Cortical Glial Cell Development - Xiaosu Li; Guoping Liu; Lin Yang; Zhenmeiyu Li; Zhuangzhi Zhang; Zhejun Xu; Yuqun Cai; Heng Du; Zihao Su; Ziwu Wang; Yangyang Duan; Haotian Chen; et al. (Neuroscience Bulletin, 2021)
Mouse cortical radial glial cells (RGCs) are primary neural stem cells that give rise to cortical oligodendrocytes, astrocytes, and olfactory bulb (OB) GABAergic interneurons in late embryogenesis. There are fundamental gaps in understanding how these diverse cell subtypes are generated. Here, by combining single-cell RNA-Seq with intersectional lineage analyses, we show that beginning at around E16.5, neocortical RGCs start to generate ASCL1 + EGFR + apical multipotent intermediate progenitors (MIPCs), which then differentiate into basal MIPCs that express ASCL1, EGFR, OLIG2, and MKI67. These basal MIPCs undergo several rounds of divisions to generate most of the cortical oligodendrocytes and astrocytes and a subpopulation of OB interneurons. Finally, single-cell ATAC-Seq supported our model for the genetic logic underlying the specification and differentiation of cortical glial cells and OB interneurons. Taken together, this work reveals the process of cortical radial glial cell lineage progression and the developmental origins of cortical astrocytes and oligodendrocytes.

Dominant factor of dry‐wet change in China since 1960s - Jinqin Xu; Dandan Wang; Xinfa Qiu; Yan Zeng; Xiaochen Zhu; Mengxi Li; Yongjian He; Guoping Shi (International Journal of Climatology, 2021)
The dry‐wet climate conditions of an area are mainly determined by the water input (e.g., precipitation, P) and output (e.g., potential evapotranspiration, PET). Based on three dry‐wet indices and the differential equation, this study designed a new attribution method to quantify the contributions of P and PET to the dry‐wet change, so as to determine the dominant factors of the dry‐wet change over whole China (CHINA) and various hydroclimate regions (i.e., arid region, AR; semi‐arid region, SAR; semi‐humid region, SHR; and humid region, HR) during 1960–2018 and six interdecadal periods. Results showed that the overall weak drying in CHINA was dominated by an increase in PET, while climate humidification in AR and HR was dominated by an increase in P, climate drying in SHR was dominated by the reduced P, and the weak drying in SAR was co‐dominated by P and PET during 1960–2018. The dominant factors of dry‐wet change over CHINA and each hydroclimate region varied in different decades. Briefly, climate humidification in CHINA and various hydroclimate regions was basically dominated by P in different decades, and the drying was mainly dominated by P in the 1960s–1980s, but the contribution of PET to climate drying began to become prominent after the 1980s. Besides, we found that P contributed more to dry‐wet change than PET on the station and regional scales, but the contribution of P to climate drying on a national scale was underestimated to some extent due to the regional offset effect of the increase/decrease in P during 1960–2018, as well as in the 1990s. These findings implied that the importance of research on the regional or local scale, and equal attention should be paid to the effects of P and PET changes in the future drought or dry‐wet change research.

Genetic and clinical determinants of mizoribine pharmacokinetics in renal transplant recipients - Rui Dai; Jingjie Li; Jingjing Wu; Qian Fu; Jiajia Yan; Guoping Zhong; Changxi Wang; Xiao Chen; Pan Chen (European Journal of Clinical Pharmacology, 2021)

Cardiac-specific LRP6 knockout induces lipid accumulation through Drp1/CPT1b pathway in adult mice - Ying Wang; Chao Yin; Zhidan Chen; Yang Li; Yan Zou; Xiang Wang; Yanpeng An; Feizhen Wu; Guoping Zhang; Chunjie Yang; Huiru Tang; Yunzeng Zou; et al. (Cell and Tissue Research, 2020)

Characterization of Shale Softening by Large Volume-Based Nanoindentation - Yunhu Lu; Yucheng Li; Yongkang Wu; Shengmin Luo; Yan Jin; Guoping Zhang (Rock Mechanics and Rock Engineering, 2020)

Lasting days contributed most to the variation of ≥ 10 °C accumulated temperature from 1961 to 2010 in China - Jinqin Xu; Xinfa Qiu; Yan Zeng; Mengxi Li; Guoping Shi; Zhe Wang; Xiaochen Zhu; Dandan Wang (Theoretical and Applied Climatology, 2019)

The distinct role of CD73 in the progression of pancreatic cancer - Liangjing Zhou; Shengnan Jia; Yan Chen; Weiming Wang; Zhengrong Wu; Weihua Yu; Mingjie Zhang; Guoping Ding; Liping Cao (Journal of Molecular Medicine, 2019)

Determination of the embedded length of stabilizing piles in colluvial landslides with upper hard and lower weak bedrock based on the deformation control principle - Changdong Li; Junfeng Yan; Junjie Wu; Guoping Lei; Liangqing Wang; Yongquan Zhang (Bulletin of Engineering Geology and the Environment, 2019)

Multiple steps determine CD73 shedding from RPE: lipid raft localization, ARA1 interaction, and MMP-9 up-regulation - Wei Zhang; Shumin Zhou; Guoping Liu; Fanqiang Kong; Song Chen; Hua Yan (Purinergic Signalling, 2018)

Comparison of two air temperature gridding methods over complex terrain in China - Guoping Shi; Zhian Sun; Xinfa Qiu; Yan Zeng; Peng Chen; Changjie Liu (Theoretical and Applied Climatology, 2018)

New method for estimating daily global solar radiation over sloped topography in China - Guoping Shi; Xinfa Qiu; Yan Zeng (Advances in Atmospheric Sciences, 2018)

Multi-point shaking table test of a long tunnel subjected to non-uniform seismic loadings - Haitao Yu; Xiao Yan; Antonio Bobet; Yong Yuan; Guoping Xu; Quanke Su (Bulletin of Earthquake Engineering, 2018)

A new 4-Amino-7-Nitro-2,1,3-Benzoxadiazole (ANBD)-Based Fluorescent Probe for the Detection of Hg2+ - Ke Wang; Xue Mao; Liling Cao; Guoping Lv; Xinfeng Dong; Yan He; Yongju Wei (Journal of Fluorescence, 2017)

Ovarian development in Argentinean shortfin squid Illex argentinus: group-synchrony for corroboration of intermittent spawning strategy - Dongming Lin; Xinjun Chen; Yong Chen; Guoping Zhu; Jizhou Yan (Hydrobiologia, 2017)

Genetic and genomic diversity of NheABC locus from Bacillus strains - Yan Cai; Tingxuan Huang; Yuekang Xu; Guoping Zhou; Ping Zou; Guifeng Zeng; Xiaojin Liu (Archives of Microbiology, 2017)

Cloning and characterization of a novel apolipoprotein gene, apolipoprotein AV, in tree shrews - Guoping Li; Huairong Luo; Guotao Sun; Guisheng Wu; Gang Wu; Yan Wang; Yong Man; Shu Wang; Jian Li; Baosheng Chen (Molecular Biology Reports, 2013)

The C161T polymorphism in the peroxisome proliferator-activated receptor gamma gene (PPARγ) is associated with risk of coronary artery disease: a meta-analysis - Zhijun Wu; Yuqing Lou; Wei Jin; Yan Liu; Lin Lu; Guoping Lu (Molecular Biology Reports, 2013)

Spermatogenesis-related ring finger gene ZNF230 promoter: identification and functional analysis - Wenming Xu; Sizhong Zhang; Weimin Qiu; Guoping He; Yunqiang Liu; Yan Sun; Yongxin Ma; Jingtao Dong; Wei Zhang (Molecular Biology Reports, 2009)

Losses of soil organic carbon under wind erosion in China - Hao Yan; Shaoqiang Wang; Changyao Wang; Guoping Zhang; Nilanchal Patel (Global Change Biology, 2005)
Soil organic carbon (SOC) storage generally represents the long‐term net balance of photosynthesis and total respiration in terrestrial ecosystems. However, soil erosion can affect SOC content by direct removal of soil and reduction of the surface soil depth; it also affects plant growth and soil biological activity, soil air CO 2 concentration, water regimes, soil temperature, soil respiration, carbon flux to the atmosphere, and carbon deposition in soil. In arid and semi‐arid region of northern China, wind erosion caused soil degradation and desert expansion. This paper estimated the SOC loss of the surface horizon at eroded regions based on soil property and wind erosion intensity data. The SOC loss in China because of wind erosion was about 75 Tg C yr −1 in 1990s. The spatial pattern of SOC loss indicates that SOC loss of the surface horizon increases significantly with the increase of soil wind erosion intensity. The comparison of SOC loss and annual net primary productivity (NPP) of terrestrial ecosystem was discussed in wind erosion regions of China. We found that NPP is also low in the eroded regions and heavy SOC loss often occurs in regions where NPP is very small. However, there is potential to improve our study to resolve uncertainty on the soil organic matter oxidation and soil deposition processes in eroded and deposited sites.